Combined Endoscopic Laparoscopic Surgery Procedures for Colorectal Surgery - Placek, Sarah B. (Clin Colon Rectal Surg, 2017)
Colonoscopy is the standard of care for screening and surveillance of colorectal cancers. Removal of adenomatous polyps prevents the transformation of adenomas to potential adenocarcinoma. While most polyps are amenable to simple endoscopic polypectomy, difficult polyps that are large, broad-based, or located in haustral folds or in tortuous colon segments can present a challenge for endoscopists. Traditionally, patients with endoscopically unresectable polyps have been referred for oncologic surgical resection due to the underlying risk of malignancy within the polyp; however, the majority of these polyps are benign on final pathology. Combined endoscopic laparoscopic surgery can help facilitate endoscopic removal of difficult lesions, or allow the surgeon to select the correct laparoscopic approach for polyp excision. Current literature suggests that these procedures are safe and effective and can potentially save patients from the morbidity of laparotomy and segmental colectomy.